The Collocation Analysis of Twilight New Moon Novel - Jimmi Jimmi; Juniato Sidauruk; Titin Suprihatin (EDULANGUE, 2019)
Nowadays in globalization era, being able to communicate in a foreign language is of paramount importance due to its role in seeking for jobs and scholarships. Translation, belonging to English for Specific Purposes, is a challenging and interesting skill to be mastered. Because of i ts rel ati ve di f fi cul ti es, it needs serious attention and concentration. The core of translation is a transfer of a message without any words missing, especially the meaning. The translator shall then be careful in replacing the words from Source Language to the Target Language. In translation, some problems appear like the usage of collocation in the novel Twilight New Moon. The author mostly uses collocation in the novel. Meanwhile, the translator translates the novel not only using word by word method, but also modulation method and the context of sentence. The use of collocation in novel makes readers find it easy to understand its meaning and acquire its message.